Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Nusa Bunga Salon Maumere - Ndoa, Maria Thantriana; Rangga, Yoseph Darius Purnama; Dimas Realino (Jurnal Projemen UNIPA, 2026)
This study aims to determine the effect of price and service quality on customer satisfaction at Nusa Bunga Salon Maumere. The research employed a quantitative approach using descriptive and verificative methods. The independent variables in this study were price (X1) and service quality (X2), while the dependent variable was customer satisfaction (Y). The population consisted of all customers of Nusa Bunga Salon Maumere who visited and utilized salon services during 2025, totaling 1,392 customers. A sample of 100 respondents was determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires, interviews, documentation, and literature studies. Data analysis was conducted using validity tests, reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), F-test, and t-test with the assistance of SPSS version 23. The results showed that, partially, price had a positive and significant effect on customer satisfaction, with a t-value of 2.803 and a significance value of 0.004. Service quality also had a positive and significant effect on customer satisfaction, with a t-value of 3.336 and a significance value of 0.001. Simultaneously, price and service quality had a positive and significant effect on customer satisfaction, with an F-value of 6.733 and a significance value of 0.002. The coefficient of determination indicated that price and service quality contributed 12.2% to customer satisfaction, while the remaining 87.8% was influenced by other factors outside the scope of this study. Based on these findings, it is recommended that Nusa Bunga Salon Maumere continuously improve its service quality and maintain affordable pricing to enhance customer satisfaction.